Psycholinguistic analysis of phonetic- phonological development of pre - school children in Lima Metropolitana - Dioses Ch., Alejandro S. (2006)
Following the approach of the phonological rules, a descriptive study was conducted of the phonetic/phonological development of pre-school students in Metropolitan Lima, who were selected by a stratified random sampling process. Data was collected with the Phonetic- Phonological Development Test composed of two areas: phonology awareness and phonology rules, evaluating consonantal and vocalic phonemes of the Spanish language. The results showed that there were significant differences in the use of phonology awareness of rhyme and alliteration according to the socio-economic level; however, the differences were not significant when considering sex and age variables. No significant differences were also found in the use of phonological rules according to sex, age and socioeconomic level.